Occurrence and Distribution of Fresh-Water Molluscs in the Riacho Fundo Creek Basin, Brasilia, Brazil - Martins-Silva Maria Júlia; Marilia Barros (Revista de Biología Tropical, 2001)
To study the distribution of molluscs in the Riacho Fundo Creek (cerrado region of central Brazil), five creek sites were sampled once every two months for one year. Molluscs were sampled using standardized kick-net sampling. Four species of molluscs were found : Physella cubensis, Melanoides tuberculata, Biomphalaria straminea and Pisidium sp. The most abundant were P. cubensis and Pisidium sp. P. cubensis was most abundant in the dry season and Pisidium sp. was most abundant in the rainy season, probably reflecting the rainy season increase of water currents Para estudiar la distribución de moluscos en Riacho Fundo Creek (region cerrado en el centro de Brazil), se muestrearon cinco sitios en un arroyo una vez cada dos meses durante un año. Los moluscos fueron muestreados usando muestreos estandarizados de "kick-net". Se encontraron cuatro especies de moluscos: Physella cubensis, Melanoides tuberculata, Biomphalaria straminea and Pisidium sp. Los más abundantes fueron P. cubensis and Pisidium sp. Physella cubensis fue la más abundante en la estación lluviosa, probablemente reflejando el aumento de corrientes de agua en la estación lluviosa